Ulcerative colitis: a case of steroid refractory disease - Lee, Lennard (BMJ Publishing Group, 2013)
A 21-year-old lady was admitted to a hospital with an 8-week history of bloody diarrhoea. She had been diagnosed with ulcerative colitis 2 years previously and had remained in remission until the gradual onset of bloody diarrhoea. Her bowel frequency was 20 times per day and associated with significant abdominal pain and weight loss. She was started on intravenous steroids, topical therapy and anti-tumour necrosis factor therapy; however, this failed to achieve symptom control. Histology of tissue obtained from flexible sigmoidoscopy eventually demonstrated cytomegalovirus (CMV)-associated colitis. Intravenous anti-viral valganciclovir was initiated and the patient made a rapid recovery. This case discusses the differentials for steroid-refractory ulcerative colitis, including the common pitfall of inflammatory bowel disease management and CMV infection. This case also discusses CMV pathophysiology including histological features, appropriate investigations and current management guidelines.